Genetic control of wood quality of myracrodruon urundeuva populations under anthropogenic disturbance - Riva, Lara Comar [UNESP]; de Moraes, Marcela Aparecida [UNESP]; Cambuim, José [UNESP]; Zulian, Daniele Fernanda [UNESP]; Sato, Luciane Missae [UNESP]; Caldeira, Francieli Alves [UNESP]; Panosso, Alan Rodrigo [UNESP]; de Moraes, Mario Luiz Teixeira [UNESP] (FapUNIFESP (SciELO), 2020)
Forest fragmentation in the Cerrado biome exposes the tree species Myracrodruon urundeuva to the risk of extinction. Thus, the objective of the study was to evaluate silvicultural characteristics related to wood quality, based on genetic parameters estimated in two M. urundeuva progenies from natural populations, assessed in Bauru-SP (PBAU) and Selvíria-MS (PSEL), 31 years after planting. The genetic parameters were estimated according to the REML/BLUP (Restricted maximum likelihood/Best Linear Unbiased Prediction) method using a mixed linear model. The progeny tests detected genetic variation. In PSEL, more positive genetic correlations and a greater number of clusters were observed. Based on the heartwood/sapwood ratio, a higher genetic gain was predicted for PBAU, and for the basic wood density, the genetic gain of the populations was approximately the same. Consequently, the areas of the two progeny tests may be used as future seed orchards to ensure wood quality and long-term ex situ conservation.
Keywords: Cerrado; Genetic conservation; Genetic variation; Risk of extinction; Seed orchard; Tree breeding